Identifikasi Konsep Matematika Dalam Permainan Tradisional Di Kampung Belajar Tanoker Ledokombo Jember - Kholil, Mohammad (IJIT: Indonesian Journal of Islamic Teaching, 2018)
An understanding of mathematical concepts can be obtained through traditional game play. Traditional games are one of the fun activities and things that are close to the kids in this elementary school students. Traditional games contain cultural values ​​that are essentially inherited heritage that must be preserved. In Jember district there is a tourist village that seeks to preserve the traditional game, the Tanoker. Researchers interested in conducting research to find out how the mathematical concepts contained in the traditional game of children used to bridge the mathematics material in school with a child's playground in the Area Learning Learning Tanoker Ledokombo District Jember District. The purpose of this research is to identify the traditional game that is played and to describe the mathematical concept that is embedded in each traditional game played by the children in the learning area of ​​Tanoker Ledokombo sub-district, Jember District. This research is descriptive qualitative research, where researcher use qualitative method with data collecting technique in form of interview, observation and documentation as triangulation form to get data and to determine the validity of data. The results are found: from the traditional game of bamboo sticks the mathematical concepts that can be learned by the students include the concept of counting, the concept of a right triangle wake-up, the concept of a unit of length, the theorem concept, the concept of linear inequality one variable; in the traditional game grang batok can be identified the concept of mathematics that is the concept of counting, the concept of wake up half-ball space, the concept of linear inequality one variable; whereas in the traditional game clogs can be identified mathematical concepts as follows the concept of hiding, the concept of parallel between two lines, and the concept of one-to-one correspondence.